The neuroligins and the synaptic pathway in Autism Spectrum Disorder. (December 2020) - Trobiani, Laura; Meringolo, Maria; Diamanti, Tamara; Bourne, Yves; Marchot, Pascale; Martella, Giuseppina; Dini, Luciana; Pisani, Antonio; De Jaco, Antonella; Bonsi, Paola
Highlights: The genetics of autism spectrum disorder is complex and heterogeneous. Neuronal communication is one of the most recurrently affected pathways. More than 30 mutations have been found in the neuroligin (NLGN) genes. Folding and trafficking of NLGNs, synaptic adhesion molecules, are impaired in ASD. NLGN animal models of ASD have shown behavioral and synaptic alterations. Abstract: The genetics underlying autism spectrum disorder (ASD) is complex and heterogeneous, and de novo variants are found in genes converging in functional biological processes. Neuronal communication, including trans-synaptic signaling involving two families of cell-adhesion proteins, the presynaptic neurexins and the postsynaptic neuroligins, is one of the most recurrently affected pathways in ASD. Given the role of these proteins in determining synaptic function, abnormal synaptic plasticity and failure to establish proper synaptic contacts might represent mechanisms underlying risk of ASD. More than 30 mutations have been found in the neuroligin genes. Most of the resulting residue substitutions map in the extracellular, cholinesterase-like domain of the protein, and impair protein folding and trafficking. Conversely, the stalk and intracellular domains are less affected. Accordingly, several genetic animal models of ASD have been generated, showing behavioral and synaptic alterations. The aim of this review is to discuss the current knowledge on ASD-linked mutations in the neuroligin proteins and their effect on synaptic function, in various brain areas and circuits.